Vortex dynamics of stratospheric sudden warmings: A reanalysis data study using PV contour integral diagnostics. (27th February 2019) - Kwasniok, Frank; Beaumont, Robin; Thuburn, John
Abstract : The dynamics of the polar vortex underlying stratospheric sudden warming (SSW) events are investigated in a data‐based diagnostic study. Potential vorticity (PV) contour integral quantities on isentropic surfaces are discussed in a unified framework; new expressions for their time evolution, particularly suitable for evaluation from data, are presented and related to previous work. Diagnostics of mass and circulation are calculated from ERA‐40 reanalysis data for the stratosphere in case‐studies of seven winters with different SSW behaviour. The edge of the polar vortex is easily identifiable in these diagnostics as an abrupt transition from high to low gradients of PV, and the warming events are clearly visible. The amount of air stripped from the vortex as part of a preconditioning leading up to the warming events is determined using the balance equation of the mass integral. Significant persistent removal of mass from the vortex is found, with several such stripping events identifiable throughout the winter, especially in those during which a major sudden warming event occurred. These stripping episodes are visible in corresponding PV maps, where tongues of high PV are being stripped from the vortex and mixed into the surrounding surf zone. An attempt is made to diagnose from the balance equation of the circulation the effect of frictional forces such as gravity wave dissipation on the polar vortex. Abstract : Stratospheric sudden warming events are a classical topic in dynamical meteorology and of major interest as stratospheric conditions may propagate down into the troposphere and affect surface weather. Here mass and circulation integral diagnostics on isentropic PV contours are introduced to monitor the polar vortex in reanalysis data. The balance equations of mass and circulation are used to diagnose mass stripping from the polar vortex as a possible preconditioning ahead of stratospheric sudden warmings as well as the effect of frictional forces such as gravity wave drag on the polar vortex.